RETRACTED Impulse Buying Intentions of Gen Z’s Consumers from Hedonic Shopping Perspective for Apparels - Agrawal, Surabhi (International Research Journal of MMC, 2024)
On 4th April 2024 this article was retracted from IRJMMC because it had already been published in the Apex Journal of Business and Management. Agrawal, S., & Pandey, A. C. (2024). Impulse Buying Intentions of Gen Z's Consumers From Hedonic Shopping Perspective for Apparels. Apex Journal of Business and Management (AJBM), 2(1), 139–149. https://doi.org/10.5281/zenodo.10896595.